2020
DOI: 10.1111/jth.14696
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory monitoring during pregnancy and post‐partum hemorrhage in women with von Willebrand disease

Abstract: Background Evidence‐based guidelines recommend that von Willebrand factor (VWF) levels be obtained in the third trimester of pregnancy to facilitate peripartum planning for women with von Willebrand disease (VWD). Objectives To identify the frequency of third trimester monitoring in a nationally representative sample of pregnant women with VWD in the United States, as well as the frequency of reproductive bleeding after pregnancy. Patients/Methods Patient data were obtained from the Truven Health MarketScan Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…While antenatal monitoring of plasma VWF levels is recommended, 13,17,18 the frequency and timing of monitoring may vary among centers 19 . Respondents advised assessment of plasma VWF levels in the third trimester most frequently (94.7%), either alone (28%), in combination with first trimester levels (29.5%), second trimester (4.5%), in all three trimesters (13.6%), or used another schedule.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…While antenatal monitoring of plasma VWF levels is recommended, 13,17,18 the frequency and timing of monitoring may vary among centers 19 . Respondents advised assessment of plasma VWF levels in the third trimester most frequently (94.7%), either alone (28%), in combination with first trimester levels (29.5%), second trimester (4.5%), in all three trimesters (13.6%), or used another schedule.…”
Section: Resultsmentioning
confidence: 99%
“…Failure to evaluate plasma VWF levels in pregnancy has been associated with higher rates of PPH at delivery. 25 As a result, both Royal (UK) and American Colleges of Obstetricians and Gynecologists (RCOG, ACOG) recommend the antenatal assessment of plasma VWF levels in women with VWD, although their guidance differs in frequency. 13,18 The RCOG advise assessment of plasma VWF levels at booking, third trimester, and prior to any invasive procedures, with the ACOG favoring third trimester assessment to facilitate delivery planning.…”
Section: Antenatal Assessment Of Plasma Vwf Levels Is Critical In Pre...mentioning
confidence: 99%
See 1 more Smart Citation
“…19 Despite these guidelines, a large U.S. sample identified that plasma VWF levels were assessed in only 32% of women with VWD in the third trimester. 41 This not only impeded care delivery but also resulted in direct clinical consequences, with a higher incidence of PPH in those whose plasma VWF levels were not reassessed (7.3 vs. 4.9%; p ¼ 0.023). 41 Prevention of PPH in women with VWD focuses on ensuring adequacy of plasma VWF and FVIII levels (as well as platelet count for patients with type 2B VWD) at the time of delivery.…”
Section: Are Fetal Precautions Required For Pregnant Women With Vwd?mentioning
confidence: 99%
“…41 This not only impeded care delivery but also resulted in direct clinical consequences, with a higher incidence of PPH in those whose plasma VWF levels were not reassessed (7.3 vs. 4.9%; p ¼ 0.023). 41 Prevention of PPH in women with VWD focuses on ensuring adequacy of plasma VWF and FVIII levels (as well as platelet count for patients with type 2B VWD) at the time of delivery. Traditionally, women with plasma VWF and/or FVIII levels < 50 IU/dL at the time of delivery will receive hemostatic support, targeting plasma VWF levels of 100 IU/dL at the time of delivery and maintaining >50 IU/dL for 3 to 7 days postpartum, depending on the mode of delivery.…”
Section: Are Fetal Precautions Required For Pregnant Women With Vwd?mentioning
confidence: 99%